Paclitaxel-coated balloon study: quantitative coronary angiography and optical coherence tomography evaluation in a swine in-stent stenosis model. (12th October 2011) - Sumida, Arihiro; Nikanorov, Alexander; Shinke, Toshiro; Li, Jinsheng; King, Spencer; Chronos, Nicolas; Hou, Dongming
Abstract : Background: Drug coated balloons (DCBs) have shown efficacy for treatment of coronary artery disease. In PEPCAD II ISR trial, paclitaxel-coated balloon (PCB) reduced in-stent restenosis (ISR) compared with paclitaxel-eluting stent (PES). Here we evaluated the efficacy of PCB in porcine ISR model. Materials and methods: 32 coronary arteries (LAD: n=12, LCX: n=11, RCA: n=9) of 12 Yorkshire pigs were assigned to two (2) groups randomly. PCB (SeQuent, length 20 mm, n=16) or non-coating balloon (NCB, length 20 mm n=16) were inflated for 60 s with B:A 1.2:1 followed by BMS (length 12 mm) implantation (S/A 1.5:1) within the target region. At 28 days, animals underwent restudy for the assessment of quantitative coronary angiography (QCA) and optical coherence tomography (OCT). Results: There were no differences between groups among all of the parameters measured by QCA and OCT. QCA late luminal loss was 1.27±0.57 mm for PCB and 1.11±0.52 mm for NCB (p=NS). Similarly, the percent of in-stent stenosis was 34.5±15.0% for PCB and 36.2±13.6% for NCB (p=NS). OCT image analysis, showed that the mean thickness of neointimal hyperplasia (NIH) on stent strut was 585±219 μm for PCB compared to 661±183 μm for NCB (p=NS), and the percent of in-stent area stenosis was 43.2±14.9% for PCB, and 49.5±11.5% for NCB (p=NS). Conclusions: In the current experimental setting, we didn't observed inhibition of neointimal formation response to PCB therapy as determined by both QCA and OCT measurement.